Explaining Accounting Structures Changes by Applying the Accounting Methodology of Radar-Polar Chart - BENEDITO, MIGUEL ANGEL PEREZ (Archives of Business Research, 2022)
The manuscript analyzes the relationship between the dynamic activity of entities and its effects on accounting structures of their financial statements. Radar charts and tetragrams visually represent the dynamic activity of features, respectively. To overcome discrepancies in qualitative and quantitative comparative analysis, the manuscript introduces polar equation parameters that drive research towards qualitative analysis. Classes of management – kinds and types - are conductor threads for explaining relations between charts and diagrams, and level of employment as well as market prices are environment variables for confirming hypothesis of manuscript. The Euclidean distances of the accounting relative centers in the tetragrams and the management optima are indicators developed for both stakeholders and managers to explain the evolution of decision making over time. The accounting applied is an economic science.